2020
DOI: 10.3389/fendo.2020.00210
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin E1 in Follicular Fluid Acts as a Potential Biomarker and Improves Oocyte Developmental Competence by Optimizing Cumulus Cells

Abstract: Metabolic profile of follicular fluid (FF) has been investigated to look for biomarkers for oocyte quality. Resolvin E1 (RvE1), a potent pro-resolving mediator, was reported to have protective action in cell function. The study aimed to examine the predictive value of RvE1 for oocyte quality and to explore the cellular mechanism of RvE1 in improving oocyte competence. Metabolic profiles of 80 FF samples showed a higher level of RvE1 in group A (blastocysts scored ≥ B3BC and B3CB according to Gardner's blastocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Interestingly, once RvE1 reached the concentration of 9.1 pg/ml in session 9, it was concurrent with the decrease in the number of produced blastocysts. This is consistent with human findings in which follicular fluid concentration of RvE1 below 8.96 pg/ml may be associated with poor oocyte quality 57 . RvE1 is an aspirin-modified cyclooxygenase-2, which is produced locally from cumulus cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, once RvE1 reached the concentration of 9.1 pg/ml in session 9, it was concurrent with the decrease in the number of produced blastocysts. This is consistent with human findings in which follicular fluid concentration of RvE1 below 8.96 pg/ml may be associated with poor oocyte quality 57 . RvE1 is an aspirin-modified cyclooxygenase-2, which is produced locally from cumulus cells.…”
Section: Discussionsupporting
confidence: 92%
“…Resolvin E1 (RvE1) is produced from omega-3 eicosapentaenoic acid and exhibits powerful anti-inflammation/pro-resolution effects in vivo 55 , 56 . RvE1 increases oocyte quality in vitro by reducing cumulus cell apoptosis and increasing cell survival and proliferation 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Feldam et al [ 33 ] demonstrated for the first time the expression of 5-, 12-, and 15-LOX in GCs isolated from women undergoing ART through the characterization of specific products derived from the metabolism of arachidonic acid (AA), such as 5-, 12-, and 15-hydroxyeicosatetraenoic acids (HETEs). In a recent study, Zhang et al [ 8 ] reported that the pro-resolving mediator resolvin E1 (RvE1) improved oocyte quality by decreasing apoptosis rate of CCs and increasing cell viability and proliferation. Considering that COX-2 and LOXs, both involved in RvE1 production, when stimulated can produce pro-inflammatory and pro-resolving mediators, we also investigated their expression in hGCs and COV434 cells by CMs of M1 and M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The LH surge activates signalling pathways in GCs of pre-ovulatory follicles associated with inflammation, such as the expression of COX-2 and 5-, 12-, and 15-LOX. These activation leads to the production of inflammatory mediators, such as eicosanoids and specialized pro-resolving mediators (SPMs), which can be found at high levels in human FF impacting on oocyte growth and quality [6][7][8]. In the ovaries, PGE 2 contributes to tissue remodelling, follicular wall proteolysis, corpus luteum formation, and regulating vascular changes.…”
Section: Introductionmentioning
confidence: 99%
“…[16] With the help of follicular fluid metabolomics, several studies have found that the amount and variety of follicular fluid metabolic components are closely related to the developmental potential and quality of oocytes. [17–19] Previous studies on this topic have shown that female follicular fluid metabolites change with an increase in age. [20] Additionally, the differences in follicular fluid metabolites between different age groups screened by follicular fluid metabolomics are involved in biological function, hormone synthesis and metabolism, oxidative stress, and other processes.…”
Section: Introductionmentioning
confidence: 99%